2019
DOI: 10.1186/s12876-019-1042-9
|View full text |Cite
|
Sign up to set email alerts
|

The HO-1-expressing bone mesenchymal stem cells protects intestine from ischemia and reperfusion injury

Abstract: Background Bone mesenchymal stromal cells (BMSC) showed protective potential against intestinal ischemia. Oxygenase-1(HO-1) could alleviate oxidative stress. In the present study, we constructed HO-1-expressing BMSC and detected the effects of it on survival, intestinal injury and inflammation following intestinal ischemia and reperfusion injury (I/R). Methods In this experiment, eighty adult male mice were divided into Sham, I/R, I/R + BMSC, I/R + BMSC/HO-1 groups. Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…There is evidence that depletion of Nrf2 increases susceptibility to liver injury [28], indicating that Nrf2 plays a major role in the hepatic protective pathway. HO-1 is a stress-induced isoform that attenuates oxidative damage, and previous studies have reported that HO-1 protects against liver, neurological, renal, and intestinal IRI [29,30]. These studies have shown that miR-141-3p regulates oxidative stress by targeting Keap1.…”
Section: Discussionmentioning
confidence: 83%
“…There is evidence that depletion of Nrf2 increases susceptibility to liver injury [28], indicating that Nrf2 plays a major role in the hepatic protective pathway. HO-1 is a stress-induced isoform that attenuates oxidative damage, and previous studies have reported that HO-1 protects against liver, neurological, renal, and intestinal IRI [29,30]. These studies have shown that miR-141-3p regulates oxidative stress by targeting Keap1.…”
Section: Discussionmentioning
confidence: 83%
“…In rats subjected to 45 min of the celiac trunk and superior mesenteric artery ischemia, followed by 60 min of reperfusion, treatment with melatonin (applied 5 min before to reperfusion) significantly reduced ischemia-reperfusion injury (neutrophil-mediated oxidative stress) as indicated by the inhibition of pathways related to ONOO − measured by the molecular probe DHR123 [75]. Yan et al used the DCFH-DA fluorescent probe to confirm the attenuation of oxidative stress induced by temporary ischemia of the superior mesenteric artery in mice treated with HO-1-expressing bone mesenchymal stromal cells (BMSC); based on the analysis using the fluorescent probe, it was concluded that BMSC that express HO-1 are more effective than treatment with BMSC alone in limiting intestinal damage and inflammation following ischemia and reperfusion injury [76]. Nagira et al used DHR123 in the monolayers of human intestinal epithelial cell line to indicate that tight junctions and dysfunction of P-glycoprotein are induced through generation of reactive oxygen metabolites by ischemia and reperfusion in vitro model, and demonstrate the use of lutein as an antioxidant [77].…”
Section: Translational Studiesmentioning
confidence: 99%
“…In addition, some studies found that the reduction of human bone MSCs can reduce the intestinal I/R injury mortality [33], and that human umbilical MSCs can provide an intestinal protective effect through nitric oxide dependent pathways [34]. Furthermore, studies have found that melatonin-supported adipose-derived MSCs [35], synergetic application of electroacupuncture and MSCs[36], HO-1-expressing BM-MSCs [37], IL-1β-activated adiposederived MSCs [38], and IL-37 gene-modi ed MSCs also have a protective effect against intestinal I/R injury [39].…”
Section: Introductionmentioning
confidence: 99%